Subjects of law and their representation: Historical review - Prelević-Plavšić Snežana; Spasojević Đorđe (Trendovi u Poslovanju)
The principle of legal equality, which assumes the equal application of legal norms to all, proclaimed by the Universal Declaration of Human Rights, has not always been in force and is the result of years of struggle. With the emergence of commodity production, the concept of persona iuris develops. The term "legal person" appeared in medieval doctrine when Hugo used it as a synonym for corporations. Representation as a legal institute that allows a representative to express the will of the represented within the limits of the given authorization, which directly binds the represented, was first defined by the German Civil Code of 1896. Since its inception, law has been a reflection of the development of society. And so, from the initial rule: alteri stipulari nemo potest, in the conditions of overall technical-technological progress where the mobility of physical and legal persons increases, and the international element is a frequent occurrence in contracts, the institute of representation gains importance.